(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the available evidence on how the promotion of mental health has been contemplated in teaching work and its relationship with continuing health education in the work environment. This is an integrative literature review, carried out through five databases and a digital library. The PICo strategy was used, with a sample composed of 4 articles, with strength of evidence IV. The results indicate that working conditions and relationships are potential generators of mental suffering, especially when conditions that make it possible to repair possible damages are not offered. There is a reflection on the mental health-promoting behaviors adopted by the teachers themselves to minimize damage from work in personal life, realizing that there is still much to debate on the subject, especially with regard to self-care. No studies were found that had permanent education as a measure implemented in the scope of teaching work, nor actions or projects for the promotion of mental health, being only mentioned as possible strategies that can contribute to the minimization of problems related to illness.